Predictors, barriers, and facilitators to refugee women’s employment and economic inclusion: A mixed methods systematic review - Areej Al-Hamad (17770842) (2024)
Refugee women’s employment and economic inclusion have emerged as significant areas of focus, with these women facing unique challenges due to their gender, refugee status, and sociocultural identities. Policymakers and researchers worldwide are giving this issue increased attention. This systematic review uses a mixed methods approach and includes 31 studies to explore the predictors, barriers, and facilitators of refugee women’s employment. The results reveal a pooled employment rate of 31.1% among refugee women. It identifies demographic features, language proficiency, education, and family structure as critical determinants of employment. The qualitative synthesis uncovers three key themes: the meaning and significance of employment; barriers to employment; and facilitators and coping for employment. This study underscores the multifaceted influences on refugee women’s employment. The findings can inform the creation of more targeted interventions, policies, and practices to support refugee women’s employment and economic integration. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0305463